COLLEGE STUDENT’S PROBLEMS IN WRITING PARAGRAPH ( A CASE STUDY AT FOURTH SEMESTER STUDENTS OF INFORMATICS MANAGEMENT OF AMIK MITRA GAMA) - Eka Melati (Universitas Mahaputra Muhammad Yamin, 2020)
The purpose of this study is to analyze problems faced by the college students of the Informatics Management study program at AMIK Mitra Gama in writing a paragraph. This study was descriptive qualitative research. The participants of this research were fourth-grade students of the Informatics Management study program attending the Applied English II course and registered on the 2018/2019 academic year, 31 students. Instrumentation of this research was student’s paragraph writing entitled “Computer in the Digital Age” in 100-150 words and interview. The result of this study found that the students had the organization of paragraph, grammatical and mechanics problems in writing a paragraph. The most typical difficulty was the organization of paragraph problems in writing concluding sentences (90,3%). Secondly, grammatical problem in using adjective (77,4%), article (64,5%), and verb (58,1%). Third, mechanics problem in punctuation (38,7%). Lastly, based on the interview, these problems arise from the students' used Google Translate more often in finishing their writing. They translated their paragraph in Bahasa Indonesia into English directly without paying attention to the aspects of writing a paragraph. It made them difficult in choosing the appropriate words. For the next study, it was suggested to further investigate another aspect of grammatical (preposition, transition word, and conjunctions) and mechanics of writing such as content and organization. It implies that writing skills should be included in course design to enhance student’s ability in writing.